2016
DOI: 10.5194/bg-13-1919-2016
|View full text |Cite
|
Sign up to set email alerts
|

Low methane (CH<sub>4</sub>) emissions downstream of a monomictic subtropical hydroelectric reservoir (Nam Theun 2, Lao PDR)

Abstract: Abstract. Methane (CH 4 ) emissions from hydroelectric reservoirs could represent a significant fraction of global CH 4 emissions from inland waters and wetlands. Although CH 4 emissions downstream of hydroelectric reservoirs are known to be potentially significant, these emissions are poorly documented in recent studies. We report the first quantification of emissions downstream of a subtropical monomictic reservoir. The Nam Theun 2 Reservoir (NT2R), located in the Lao People's Democratic Republic, was floode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…At the NT2R, diffusive CH 4 fluxes covered the whole range of fluxes reported for tropical reservoirs, depending on the season. Most of the fluxes at the NT2R were around 1 order of magnitude lower than those at Petit Saut Reservoir (French Guiana) just after the impoundment (Galy-Lacaux et al, 1997), and of the same order of magnitude as reported for reservoirs 10 to 18 years older (Abril et al, 2005;Guérin et Kemenes et al, 2007;Chanudet et al, 2011). However, some diffusive fluxes at stations RES1-8 in the WW and CD seasons (up to 202 mmol m −2 d −1 ) are among the highest ever reported at the surface of a hydroelectric reservoir or a lake (Bastviken et al, 2011;Barros et al, 2011) and rivers downstream of dams (Abril et al, 2005;Guérin et al, 2006;Deshmukh et al, 2016).…”
Section: Spatial and Seasonal Variability Of Surface Ch 4 Concentratisupporting
confidence: 54%
See 1 more Smart Citation
“…At the NT2R, diffusive CH 4 fluxes covered the whole range of fluxes reported for tropical reservoirs, depending on the season. Most of the fluxes at the NT2R were around 1 order of magnitude lower than those at Petit Saut Reservoir (French Guiana) just after the impoundment (Galy-Lacaux et al, 1997), and of the same order of magnitude as reported for reservoirs 10 to 18 years older (Abril et al, 2005;Guérin et Kemenes et al, 2007;Chanudet et al, 2011). However, some diffusive fluxes at stations RES1-8 in the WW and CD seasons (up to 202 mmol m −2 d −1 ) are among the highest ever reported at the surface of a hydroelectric reservoir or a lake (Bastviken et al, 2011;Barros et al, 2011) and rivers downstream of dams (Abril et al, 2005;Guérin et al, 2006;Deshmukh et al, 2016).…”
Section: Spatial and Seasonal Variability Of Surface Ch 4 Concentratisupporting
confidence: 54%
“…with C CH 4 the CH 4 concentration, S CH 4 -ox the specific CH 4-ox from Deshmukh et al (2016), C O 2 the oxygen concentration, K m(O 2 ) the half-saturation constant (K m ) of O 2 for CH 4 oxidation, d depth of the water layer, and I (z) the inhibition of methanotrophic activity by light as defined by Dumestre et al (1999) at the Petit Saut Reservoir. Finally, the CH 4 oxidation rates were integrated in the oxic water column, from the water surface to the limit of oxygen penetration.…”
Section: Aerobic Ch 4 Oxidationmentioning
confidence: 99%
“…2) are driven by bubbles (see Supplementary Table S4). In contrast to other studies 21,24 , we found that bubbles occurred in the deep-water zone (>10 m) rather than in the shallow zone (<5 m), and we suggest that the high ebullitive CH 4 emissions from deep water zones are related to heterogeneous sediment accumulation 12,13 because little or no sediment accumulates along reservoir margins 39 .…”
Section: Discussioncontrasting
confidence: 99%
“…The rapid stream of water increases the water current velocity, which enhances the gas transfer velocity at the air-water interface and improves downstream CH 4 emission flux 22 . 50% of the total CH 4 emissions recorded downstream from the Balbina Reservoir in Brazil 18 represented approximately 30% of the total greenhouse gas emissions from the eight reservoirs in the dry tropical biome region of the country 23 , whereas downstream emissions accounted for 10% of the total CH 4 emissions from the Nam Theun 2 Reservoir in Laos 24 .…”
Section: Introductionmentioning
confidence: 99%
“…5a) compared to the CD season from 2009 to 2012. The average CO 2 emissions in 2009 and 2010 and to a lesser extend 2011 are in the same range as emissions from the Petit Saut Reservoir during the first 5 years after impoundment (Abril et al, 2005), and in the upper range of average CO 2 diffusive fluxes measured in older tropical reservoirs (dos Santos et al, 2006;Kemenes et al, 2011;Yang et al, 2013) or in young boreal reservoirs (Teodoru et al, 2011;Tadonléké et al, 2012). In 2012 and 2013, emissions from NT2R by diffusive fluxes are still higher than most of the older Asian reservoirs (Wang et al, 2011;Chanudet et al, 2011;Xiao et al, 2013;Zhao et al, 2013;Panneer Selvam et al, 2014) and other Brazilian reservoirs flooding savannah (Roland et al, 2010;Pacheco et al, 2015).…”
Section: Total Co 2 Emissions From the Nam Theun 2 Reservoirmentioning
confidence: 62%